Partisipasi Petani Padi dalam Program Asuransi Usaha Tani Padi di Desa Bulukarto Kecamatan Gadingrejo Kabupaten Pringsewu - Taufiqurrahman, M.S; Nikmatullah, Dewangga; Syarif, Yuniar Aviati (Suluh Pembangunan : Journal of Extension and Development, 2022)
This research aims to find out the level of participation of rice farmers in the AUTP Program, and factors related to the participation of rice farmers in the AUTP Program. This research was conducted in Bulukarto Village, Gadingrejo District, Pringsewu Regency. Data collection on this study was conducted in June-July 2021. The respondents to this study were 82 rice farmers who were members of the farmer group. The study used survey methods, descriptively analyzed data and Rank Spearman statistics. The results showed that participation in the planning stage was in the low category, while the participation of the program implementation, evaluation, and utilization of results was in the high category. Factors related to farmer participation are: Formal education, farmer motivation, knowledge of the program, number of family dependents, and frequency of follow-up counseling. Keywords: participation, rice farmers, AUTP program